Evidence of preferential female prevalence of HTLV-I associated tropical spastic paraparesis in Bahia-Brazil - O. A. Moreno-Carvalho; J. I. Santos; G. Di Credico; B. Galvão-Castro (Arquivos de Neuro-Psiquiatria)
In order to evaluate the prevalence of HTLV-I infection and its association with tropical spastic paraparesis (TSP) in Bahia, a Northeastern State of Brazil, CSF and sera from TSP patients and CSF and/or sera from some selected groups of individuals were studied. The results seem to indicate a higher prevalence of HTLV-I infection in women than men with TSP and among individuals of HIV risk groups. Some alterations of routine analysis of CSF can suggest HTLV-I infection in TSP patients.